Financial Literacy as A Character-Based Education for Students: A Bibliometric Analysis - Marlia, Sri (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2024)
Consumerism, fueled by digitalization and pay-later mechanisms, often leads to unwise spending behaviors, reflecting a lack of financial literacy (Lusardi & Mitchell, 2014). This study emphasizes financial literacy as a form of character-based education to foster responsible financial behaviors among students. Prior research highlights that financial literacy positively influences decision-making and long-term financial well-being (OECD, 2016). However, comprehensive bibliometric analyses focusing specifically on students' financial literacy and its integration with character-based education remain limited. This study addresses this gap by systematically analyzing 745 articles published between 2000 and 2024, sourced from the Scopus database, using inclusion and exclusion criteria. Utilizing VOSviewer software, the bibliometric analysis identifies key trends, significant authors, research gaps, and dominant themes within the field. The findings reveal the existing studies on financial literacy has been expanded, not only on the various topics in finance, but also interdisciplinary fields. However, it has found only small integration with character-based education. This study contributes to the literature by offering a structured overview of research trends, gaps and actionable insights for enhancing students’ financial literacy and well-being through targeted educational programs and policies particularly and its integration with character-based education.